Pengaruh Jenis Fungi Mikoriza Arbuskula dan Konsentrasi Pupuk Organik Cair Yomari Terhadap Pembibitan Kelapa Sawit (Elaeis guineensis Jacq) Pada Media Bekas Tambang Kapur - Ameilia, Reja; Syarif, Auzar; Dwipa, Indra (JURNAL AGROTEKNOLOGI UNIVERSITAS ANDALAS, 2025)
The use of ex-limestone mining land as an alternative planting medium requires technological innovation to overcome nutrient limitations and unfavorable soil conditions. This study aims to determine the effect of Arbuscular Mycorrhizal Fungi (AMF) types and Yomari liquid organic fertilizer (POC) concentrations on the growth of oil palm (Elaeis guineensis Jacq.) seedlings at the pre-nursery stage in limestone mining waste soil. This experimental research was conducted in February - May 2025. The experiment was conducted at the Experimental Garden UPT, Faculty of Agriculture, and Plant Physiology Laboratory, Faculty of Agriculture, Andalas University, Padang. The design used was a factorial Completely Randomized Design (CRD) with two factors, namely the type of AMF (Glomus sp., Gigaspora sp., and a combination of Glomus sp. x Gigaspora sp.) and the concentration of Yomari POC (0; 0.5; 1.0; and 1.5 mL L⁻¹) which were each repeated three times, resulting in 36 experimental units. Each experimental unit consisted of 9 plants, with 5 samples for destructive observation and 4 samples for non-destructive observation, resulting in a total of 324 sample plants. The results showed no significant interaction between AMF types and POC concentrations on all growth parameters. However, individually, the AMF Glomus sp. type proved to be the most effective in supporting the growth of oil palm seedlings, as indicated by a high percentage of root colonization, increased phosphorus (P) uptake, and an increase in root length and volume. Meanwhile, the application of POC Yomari at a concentration of 1.0 mL L⁻¹ resulted in the best seedling growth, indicated by an increase in P uptake parameters, root length, and root volume. This indicates that the application of Glomus sp. AMF and POC Yomari at a dose of 1.0 mL L⁻¹ is effective in supporting the growth of oil palm seedlings in post-limestone mine soil media. In addition, the results of this study provide a scientific basis for the use of arbuscular mycorrhizal fungi and liquid organic fertilizer as a sustainable soil management strategy for post-mining land rehabilitation and improvement of oil palm nursery practices.